2021
DOI: 10.14393/bj-v37n0a2021-56306
|View full text |Cite
|
Sign up to set email alerts
|

Determination of bioactive compounds, antimicrobial activity, and the phytochemistry of the organic banana peel in Thailand

Abstract: Banana fruit is enriched with phytonutrients, minerals, and its peel, which is mostly discarded as waste. This research aimed to study its bioactive compound properties, antimicrobial activity, and identify and characterize the constituents of organic banana peel extract (BPE), composed of six species (i.e., Kluai Homthong, Kluai Namwa, Kluai Kai, Kluai Hukmook, Kluai Lebmuernang, and Kluai Homtaiwan). Total phenolic content (TPC), antioxidant content, and ferric-reducing antioxidant power (FRAP) were importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Accordingly, the L. sakei powder was packed with polyethylene material at a ratio of 1:3 to preserve its treatment e cacy. From an industrial point of view, using probiotic powder instead of bacteria culture is preferred due to the higher viability of the product during storage and the ease of use (NAKSING et al, 2019;Oktavia et al, 2020). In addition, our data showed that L. sakei powder had higher e cacy in an in vivo model than L. sakei culture.…”
Section: Discussionmentioning
confidence: 68%
“…Accordingly, the L. sakei powder was packed with polyethylene material at a ratio of 1:3 to preserve its treatment e cacy. From an industrial point of view, using probiotic powder instead of bacteria culture is preferred due to the higher viability of the product during storage and the ease of use (NAKSING et al, 2019;Oktavia et al, 2020). In addition, our data showed that L. sakei powder had higher e cacy in an in vivo model than L. sakei culture.…”
Section: Discussionmentioning
confidence: 68%
“…Banana peel is an abundant source of dietary fiber, proteins, lipids, pectin, essential amino acids, polyunsaturated fatty acids, and micronutrients, in addition to other bioactive compounds ( Ibiyinka et al, 2021 , Khawas and Deka, 2016 , Naksing et al, 2021 ). Regardless of the fruit type (climacteric or non-climacteric), fruit ripening ultimately leads to transformations like cell wall softening, accumulation of sugars and phenolic compounds, color changes (anthocyanin and carotenoid accumulation), and the formation of aroma and volatile compounds.…”
Section: Resultsmentioning
confidence: 99%
“…rosenbergii (Rattanavichai & Cheng, 2014). It has been suggested that the extract of BP could be applied as a supplement to animal and aquatic feed in order to enhance the growth and immunity of prawns (Naksing et al, 2021; Rattanavichai & Cheng, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The Fourier‐transform infrared spectroscopy (FTIR) (iD7ATR; Thermo Scientific) was performed to specify the functional groups of phytochemicals of different crude organic BPE following the method of Naksing et al (2021). The translucent sample discs were prepared by mixing 10 mg KBr salt and 1 mg freeze‐dried powder of different BPE.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation